2001
DOI: 10.1002/jmri.1172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anatomical and functional properties of deglutition with various kinetic high‐speed MRI sequences

Abstract: We evaluated various fast MR sequences for obtaining anatomical and dynamic functional information during deglutition. Seven healthy volunteers underwent MRI of the oropharynx during swallowing of an oral positive-contrast agent. Single-slice imaging was performed in the median sagittal plane while subjects were in a supine position. Twenty serial images were obtained using EPI, FLASH, and turbo-FLASH sequences. The dynamic (movement-related) information and the anatomical resolution of the soft tissues were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 13 publications
0
70
0
4
Order By: Relevance
“…The correct posture of the tongue (Van Dyck et al, 2016) seems one of the most promising solutions to this problem, further stressing the importance of tongue in the rehabilitation from oral disorders. Therefore, it could be possible that the physiological asymmetries in the masticatory system of the studied human group is attributable to the posture of the tongue which, in addition to all other muscles involved in swallowing, exerts a force that is absorbed by the hard palate (Anagnostara et al, 2001; Hartl et al, 2003; Lear et al, 1965; Mosier et al, 1999; Palmer et al, 2008; Pameijer et al, 1970). When swallowing takes place correctly, the tip of the tongue presses firmly against the roof of the mouth or hard palate, which is located slightly behind the front teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The correct posture of the tongue (Van Dyck et al, 2016) seems one of the most promising solutions to this problem, further stressing the importance of tongue in the rehabilitation from oral disorders. Therefore, it could be possible that the physiological asymmetries in the masticatory system of the studied human group is attributable to the posture of the tongue which, in addition to all other muscles involved in swallowing, exerts a force that is absorbed by the hard palate (Anagnostara et al, 2001; Hartl et al, 2003; Lear et al, 1965; Mosier et al, 1999; Palmer et al, 2008; Pameijer et al, 1970). When swallowing takes place correctly, the tip of the tongue presses firmly against the roof of the mouth or hard palate, which is located slightly behind the front teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Anagnostara et al (5) reported that the turbo fast low-angle shot (Turbo-FLASH) sequence achieved 0.15-0.3 seconds/ slice using a 1.5T MRI system (Gyroscan ACS-NT; Philips Medical Systems, Best, The Netherlands). Barkhausen et al (10) reported that the true fast imaging with steady precession (TrueFISP) sequence produced 0.139 -0.405 seconds/image using a 1.5T MRI system (Magnetom Vision, Siemens, Erlangen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…This technique, however, requires food or drink to be mixed with a contrast agent for MRI. The toxicity of gadolinium in cases of aspiration remains to be clarified 1,4) . Single-shot fast spin echo, on the other hand, better facilitates evaluation of deep structures and mobility during dry swallows 6,8) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in MRI mean that it can now capture the motions of soft tissues during swallowing. Various high-speed MRI techniques such as echo-planar imaging, turbo-fast low-angle shot (turbo-FLASH), and single-shot fast spin echo, have been used for dynamic imaging of soft tissues during physiological motions 1,4,[6][7][8]10,11) . However, none of these methods allows full capture of movement during the pharyngeal phase, in which movements take less than 1 sec.…”
Section: Introductionmentioning
confidence: 99%